CRIMES OF TERRORIST ORIENTATION ACCORDING TO THE CRIMINAL LEGAL ANALYSIS OF UKRAINE - Lysko, Tetiana; Shylova, Kristina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to clarify the concept of terrorism, to define the content of terrorist-oriented crimes and the composition of crimes provided for in Article 258, 258-1 – 258-5 of the Criminal Code of Ukraine. Research methods: system analysis method, dialectical method of scientific knowledge, historical-cultural method, structural-functional and comparative approaches in the analysis of political and social phenomena. Results: the posed questions allow to investigate the application of anti-terrorist legislation, as well as ways of its improvement regarding the qualification of crimes of a terrorist orientation as complex phenomena that have acquired new forms and manifestations in modern conditions. The result was a generalization of scientific, theoretical and practical work on establishing criminological determinants of terrorism, determining their place and role in carrying out terrorist activities by criminal organizations, organized groups. On the basis of the analysis of the current state of the criminal-legal countermeasures against terrorism in Ukraine, it was established that the current legislative framework, although it needs some improvement taking into account the consequences of conducting an anti-terrorist operation in the country, is generally quite sufficient to implement the principle of inevitability of criminal responsibility for crimes of a terrorist nature. Discussion: consider the theoretical issues of forming the characteristics of terrorist-oriented crimes in the structure of the investigation methodology, taking into account such research questions as: defining the concept of "terrorist-oriented crimes" taking into account the scientific approaches of various scientists. To characterize the concept in both the narrow and broad and most broad meanings of this word. Provide signs that are inherent in terrorism. To determine the place of criminalistic characteristics of crimes of a terrorist orientation in the structure of the methodology of crime investigation and justify the need for its application.